ВПЛИВ ПОРОШКІВ НТМ НА СТРУКТУРНІ ПЕРЕТВОРЕННЯ В СКЛОКОМПОЗИТАХ ПРИ ТЕРМООБРОБЦІ - Кухаренко, Світлана (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2019)
The main results of the study of the effect of diamond and cubonite powders on structural transformations in silicate multicomponent systems, which are widely used in instrumental composite materials on ceramic binders, are presented. The introduction of the AСM 10/7 diamond micropowders has been shown to increase the wear resistance of the glass composite 1.3 times.